Опыт Республики Польша и Республики Азербайджан, связанный с переходом на международные стандарты финансовой отчетности (МСФО): возможность использования для Республики Беларусь. - Гриб (Gryb N.G.), Н.Г. (Экономика и банки, 2015)
Целью исследования явилось изучение практического опыта Республики Польша и Республики Азербайджан по переходу на международные стандарты финансовой отчётности (МСФО). В контексте данной проблемы рассматривается вопрос, связанный с разработкой целого комплекса мероприятий по внедрению МСФО. Автор приходит к выводу о необходимости поэтапной реализации реформы бухгалтерского учёта Республики Беларусь, акцентирует внимание на основных проблемах, препятствующих достижению поставленной цели. = At the present time everyone understands the fact that no nation in the world can develop successfully without integration into the global economy. In accordance with the State program of transition to international accounting standards adopted by the Council of Ministers of the Republic of Belarus № 694 of May 4, 1998 a period of Belarusian organizations and individual entrepreneurs transition to the international financial reporting standards before January 1, 2008 in the Republic of Belarus was fixed. Realization of this program requires much work with the regulatory framework. On the practical implementation of IFRS the experience of Poland and Azerbaijan may be the most appropriate example of understanding of what problems arise during the transition to IFRS, and how to solve them. This paper reveals the main steps and methods of accounting reforms in each of these countries. The transition to IFRS is connected with substantial costs for businesses. For this reason the State must create all necessary conditions to facilitate this process.